Innovation of digital multimedia: recognizing the advantages / Azyan Yusra Kapi @ Kahbi ... [et al.] - Kapi @ Kahbi, Azyan Yusra; Suhaimi, Azrina; Hasmy, Harshida; Ab Jabal, Mohamad Faizal (2023)
This study explores the effectiveness of an innovative multimedia application as a teaching tool for improving students' understanding of C++ functions. The intervention incorporated advanced visualization techniques and rich multimedia elements to create a dynamic learning experience. The primary objective was to assess the intervention's impact on students' comprehension and evaluate its educational significance. A total of 33 participants underwent pre-test and post-test assessments, with the normalized gain (N-Gain) serving as the key metric for improvement. The calculated N-Gain was approximately 0.6336, indicating a moderate improvement in students' performance following the intervention. The discussion interprets the N-Gain in the context of the study's objectives and practical implications. Notably, the study underscores the e-content application's effectiveness in achieving educational goals and its potential for broader implementation in computer science education. Despite limitations such as sample size and context-specific factors, this research highlights the importance of innovative educational approaches in the digital age. It contributes to the evolving landscape of educational technology and pedagogy, offering valuable insights for educators aiming to create engaging and impactful learning experiences in computer science and related fields.